The utility and safety of diode laser in endoscopic stapes surgery - Yuvatiya Plodpai (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objective The advantages of laser stapedotomy are less trauma and more precise and minimally invasive techniques; however, the potential risk of overheating from the laser combined with the endoscope tip must be considered. This study aimed to assess the efficacy and safety of diode lasers for endoscopic stapes surgery. Methods A retrospective review of 56 patients with otosclerosis who underwent primary endoscopic stapedotomy with a diode laser from 2017 to 2020 was conducted. Demographic data, intraoperative findings, preoperative and postoperative audiological assessments, and postoperative complications were analyzed. Results There was no statistically significant difference between the preoperative and postoperative bone conduction thresholds. The mean postoperative air‐bone gap (ABG) improved significantly compared to the preoperative ABG (4.07 vs. 35.43 dB, p < .001). The postoperative ABG closure within 10 dB at 6 and 12 months was achieved in 87.50% and 91.07% of patients, respectively. The postoperative pain scores at 4 and 24 h were 2.55 and 0.39, respectively. Immediate postoperative vertigo was reported in 12.50% of patients, with 100% complete recovery 2 months after surgery. The chorda tympani nerve was preserved in all the cases. Postoperative taste disturbances at 2 and 12 months were observed in 17.86% and 1.79% of patients, respectively. Conclusion The diode laser in endoscopic stapedotomy is a safe and effective technique that provides satisfactory hearing outcomes. Temporary taste disturbances during the early postoperative period are a concern. The handheld diode laser delivery system is suitable for an endoscopic approach and is an alternative armamentarium for the treatment of otosclerosis. Level of evidence: IV.